The Transformation of Contract Law in the Era of Digital Contracts in Indonesia - Fikrina, Aulia; Putri Deswari, Meissy; Sucia, Yossiramah; Silvia Putri, Amanda (Magister Ilmu Hukum Fakultas Hukum Universitas Riau, 2025)
This study examines the transformation of contract law in Indonesia in response to the increasing prevalence of digital agreements and automated contracts, particularly smart contracts. The central issue addressed is the adaptability of conventional legal paradigms to digital interactions, wherein agreements are frequently formed and executed through code without direct human negotiation. Employing a normative-qualitative method and a comparative conceptual approach, the research identifies key challenges and legal gaps in the recognition, validity, and enforcement of digital contracts. The findings indicate that, although digital contracts have gained some legal recognition, existing doctrines remain anchored in traditional principles, which are inadequate for regulating autonomous contract execution and digital evidentiary mechanisms. The study's contribution lies in proposing a paradigm shift: contract law must evolve beyond merely accepting digital formats to reinterpreting core principles—such as consent, freedom of contract, and legal certainty—within algorithmic frameworks. This necessitates a reorientation of legal thought, recognizing technology not only as a medium but as an influential actor in legal relationships. The study offers a critical theoretical and regulatory framework to support the development of responsive and equitable contract law in the digital age.